Materiality and the mediating roles of eHealth: A qualitative study and comparison of three cases. (July 2022) - Frennert, Susanne; Petersson, Lena; Muhic, Mirella; Rydenfält, Christofer; Nymberg, Veronica Milos; Ekman, Björn; Erlingsdottir, Gudbjörg
Against the backdrop of eHealth solutions increasingly becoming a part of healthcare professionals' ways of doing care work, this paper questions how the solutions mediate the experience of healthcare professionals when deployed. We undertook a qualitative study of three eHealth solutions, conducting qualitative interviews with a diverse sample of 102 healthcare professionals from different care settings across the south of Sweden. Materiality and postphenomenology serve as analytic tools for achieving an understanding of the mediating roles of eHealth solutions. The analysis emphasises the mediating roles consisting of interrelated paradoxes: (1) changing and perpetuating boundaries between patients and professional groups, (2) (dis)enabling augmented information and knowledge processes and (3) reconfiguring professional control over work. This contribution provides critical insights into materiality as a category of analysis in studies on the deployment of eHealth solutions, as these technologies have both intended and unintended consequences for care work. Our study identified general positive consequences of all three solutions, such as the increased feeling of closeness to patients and colleagues over time and space; increased 'understanding' of patients through patient-generated data; and increased autonomy, due to the fact that asynchronous communication makes it possible to decide when and which patient to attend to. We also identified general unintended consequences of the solutions, such as maintenance of power relations maintained due to organisational structures and professional relations, disabled information and knowledge processes due to the lack of non-verbal clues, reduced professional autonomy due to technical scripts determining what data is collected and how it is categorised, and uneven workload due to the dependency on patient input and compliance.